Acute Thigh Compartment Syndrome due to an Occult Arterial Injury Following a Blunt Trauma: A Case Report. Issue 1 (January 2020) - Nooh, Anas; Wang, Casey K.; AlAseem, Abdulrahman; Harvey, Edward J.; Bernstein, Mitchell
Abstract : Case: We report a 27-year-old man who presented with thigh swelling and inability to bear weight after blunt trauma 24 hours before. Based on the clinical assessment, the patient was diagnosed with anterior compartment syndrome of the thigh and underwent fasciotomy. Postoperatively, 1.5 L of blood were drained from his wound in the first 30 minutes after the operation. Angiography was performed demonstrating bleeding from the lateral femoral circumflex which was successfully embolized. Conclusions: Our case represents the underlying arterial injury that was initially undiagnosed as a cause for thigh compartment syndrome. Physicians should consider associated injuries (beyond muscle crush) when making a diagnosis of compartment syndrome.